Psychological and Emotional Effects of Digital Technology on Digitods (14–18 Years): A Systematic Review - Limone, Pierpaolo; Toto, Giusi Antonia (Frontiers in Psychology, 2022)
Background: The use of smartphones and other technologies has been increasing in adolescents aged 14–18 years old. To further explain this relationship and explore the gap in research, this paper will appraise the available evidence regarding the relationship digital technology use and psychological/emotional outcomes and report on the strength of the associations observed between these variables. Methodology: To select relevant studies, five separate computerised searches of online and electronic databases were performed. These included PubMed (MEDLINE, National Library of Medicine), ScienceDirect, Cochrane, Scopus, and Web of Science to attain literature from January 2017 to April 2022. The author independently reviewed studies for eligibility as per the inclusion/exclusion criteria and extracted the data according to a priori defined criteria. Risk of bias was assessed using the Agency for Healthcare Research and Quality (AHRQ) for healthcare studies and Cochrane Risk Of Bias In Non-randomized Studies of Interventions (ROBINS-I) assessment tool. Results: Seven studies were included in this review. A positive relationship was found between excessive digital technology usage and negative psychological and emotional outcomes in adolescents aged 14–18 (p ≤ 0.005). A statistically significant difference was found between girls and boys, with girls experiencing more negative outcomes than boys. Conclusions: As the evidence in this review is distinctive, it is imperative that further research be conducted to investigate any synergistic relationships among these variables on a larger scale in order to better advise public health initiatives to specifically target heightened digital technology usage in adolescents.